DETERMINANTS OF THE DECISION TO BECOME A CUSTOMER OF BANK MUAMALAT KC KEDIRI - Ilma Sufia; Yayuk Sri Rahayu (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2024)
This study aims to determine the effect of Islamic branding, product quality, personal selling, and digital marketing on customer decisions. The research methodology used is a quantitative approach. Using accidental sampling and purposive sampling methods . The data used in this study are data from questionnaires distributed to customers of Bank Muamalat KC Kediri which are used as research objects. The number of samples used in this study were 148 respondents. In this study using multiple linear regression analysis. The results showed that partially Islamic branding, product quality, and digital marketing variables had no significant effect on the decision to become a customer. However, the personal selling variable partially has a significant effect on the decision to become a customer. The conclusion of this study is that partially the personal selling variable has a significant effect on the decision to become a customer of Bank Muamalat KC Kediri. While the variable Islamic branding, product quality, digital marketing has no significant effect on the decision to become a customer of Bank Muamalat KC Kediri. And simultaneously the four variables have a positive and significant effect on the decision to become a customer of Bank Muamalat KC Kediri.